Peningkatan Literasi Kesehatan tentang TBC melalui Edukasi Interaktif di Unit Rawat Jalan dan Poli TB UPT Puskesmas DTP Saketi - Ucu Wandi Somantri; Frida Elasjulia; Laela Nina Isna Asaro; Chaerunissa Agustina; Kokom Komalasari; Puspita Puspita; Erma Noor Wahyuningsih; Heny Sasmita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Tuberculosis (TB) remains one of the leading infectious diseases causing morbidity and mortality in Indonesia. Limited public health literacy regarding TB symptoms, prevention, and treatment adherence contributes to delayed diagnosis and poor treatment outcomes. This community service program aimed to improve public understanding and awareness of TB through interactive educational activities conducted at the Outpatient Unit and TB Clinic of UPT Puskesmas DTP Saketi, Pandeglang Regency. The activities involved 30 participants, including TB patients and their families. Interactive counseling sessions, audiovisual media presentations, and group discussions were used to engage participants actively. Evaluation results showed a 35% increase in participants’ knowledge scores, greater awareness of the importance of completing treatment, and improved communication between patients and healthcare workers. The implementation of interactive education proved effective in enhancing TB health literacy and supporting national TB elimination efforts at the primary healthcare level.